2021
DOI: 10.3389/fphar.2021.659577
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effectiveness and Safety of Repurposing Drugs for the Treatment of COVID-19: Position Standing in 2021

Abstract: COVID-19, transmitted by SARS-CoV-2, is one of the most serious pandemic situations in the history of mankind, and has already infected a huge population across the globe. This horrendously contagious viral outbreak was first identified in China and within a very short time it affected the world's health, transport, economic, and academic sectors. Despite the recent approval of a few anti-COVID-19 vaccines, their unavailability and insufficiency along with the lack of other potential therapeutic options are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 155 publications
(192 reference statements)
0
29
0
1
Order By: Relevance
“…Remdesivir, a nucleotide analog that resembles adenosine triphosphate (ATP) and thus inhibits virus RNA synthesis, was considered a potential treatment option for RNA viruses, including SARS-Cov-2. Initial clinical reports indicated clinical and antiviral efficacy as a part of multidrug therapy in severe COVID-19 cases [ 75 ]. However, a recent meta-analysis showed that remdesivir had no effect on mortality in hospitalized COVID-19 patients [ 76 ] but may increase the recovery percentage and decrease the ventilation requirement rate.…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…Remdesivir, a nucleotide analog that resembles adenosine triphosphate (ATP) and thus inhibits virus RNA synthesis, was considered a potential treatment option for RNA viruses, including SARS-Cov-2. Initial clinical reports indicated clinical and antiviral efficacy as a part of multidrug therapy in severe COVID-19 cases [ 75 ]. However, a recent meta-analysis showed that remdesivir had no effect on mortality in hospitalized COVID-19 patients [ 76 ] but may increase the recovery percentage and decrease the ventilation requirement rate.…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…Given that currently there is no effective treatment for COVID-19 [ 3 , 12 ], a prophylactic intervention via vaccination is deployed via a worldwide campaign. The BNT162b2 mRNA vaccine (Comirnaty TM ; Pfizer-BioNTech GmbH) is the first vaccine that received emergency use authorization by both FDA and EMA, due to its efficacy in healthy adults [ 13 ], while reportedly it also induces cross-neutralization of at least some of the circulating SARS-CoV-2 variants [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the COVID-19 pandemic spreads globally, research scientists and policymakers are making continual efforts to curtail the transmission by consistent public health interventions, such as through the use of a nose mask, washing of hands, social distancing, testing of suspected cases, and isolation [ 82 , 83 ]. Interestingly, repurposed drugs, such as remdesivir, ritonavir, chloroquine, and lopinavir, among others, are being used in the management of COVID-19 infection [ 84 ]. In addition, the use of supplements that can boost the host immune system has been documented as a good strategy to fight the virus [ 85 ].…”
Section: Pharmacological Potentials Of C Volubilementioning
confidence: 99%